2018
DOI: 10.3389/fpubh.2018.00240
|View full text |Cite
|
Sign up to set email alerts
|

How Social Networks May Influence Cancer Patients' Situated Identity and Illness-Related Behaviors

Abstract: Little research is currently available that captures variation in the degree to which individuals who have, or had cancer in the past (but are in remission) integrate their cancer experience into their sense of self or their cancer-associated identity. Such research should cover how those identities shape personal narratives within existing or new social networks so that, ultimately, we understand the implications for treatment choices and health outcomes. Particularly understudied are the social factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…En general, las redes sociales ofrecen apoyo no solo a pacientes, sino también sus cuidadores (Bender et al, 2013;Jones et al, 2018;Zade et al, 2017); mejoran el acceso a conocimientos sobre el tratamiento y sobre su impacto tanto físico como emocional (Attai et al, 2015;Gentile et al, 2018;Moorhead et al, 2013); y ayudan a los pacientes a vivir con el cáncer después del tratamiento (Banerjee et al, 2018).…”
Section: Las Redes Sociales Como Plataforma Para La Visibilidad Del C...unclassified
“…En general, las redes sociales ofrecen apoyo no solo a pacientes, sino también sus cuidadores (Bender et al, 2013;Jones et al, 2018;Zade et al, 2017); mejoran el acceso a conocimientos sobre el tratamiento y sobre su impacto tanto físico como emocional (Attai et al, 2015;Gentile et al, 2018;Moorhead et al, 2013); y ayudan a los pacientes a vivir con el cáncer después del tratamiento (Banerjee et al, 2018).…”
Section: Las Redes Sociales Como Plataforma Para La Visibilidad Del C...unclassified
“…We also included nine articles in the review that did not include primary data: articles mentioned in refs. [6,15,26,27,31 && , 58,63,67,69] were reviews or commentaries of various kinds. Not all of those articles labeled as reviews are full systematic reviews, and include editorials and viewpoints.…”
Section: Key Pointsmentioning
confidence: 99%
“…Additionally, there is accumulating evidence on the importance of social networks for health status. It was found that higher levels of social integration, such as more frequent contact with friends, family, neighbors, etc., have been associated with better physical health and fewer morbidities such as hypertension [ 34 ], heart disease [ 14 ], diabetes [ 35 ] and cancer [ 36 ]. Social networks were associated with lower overall mortality as they contributed to a reduction in deaths from cardiovascular disease, and strong social networks were linked to a lower incidence of stroke, and potential benefits in extending the survival rates of men with coronary heart disease [ 37 ].…”
Section: Introductionmentioning
confidence: 99%